Ethnobotany Home garden in Puspa Jagad Tourism Ecology Area Semen Village, Gandusari District, Blitar Regency - Purnomo Purnomo; Jati Batoro; Abdul Hakim (Program Pascasarjana, 2019)
Home garden is one form of sustainable agricultural land management. Home garden is important as a local identity in a society especially in rural areas. The purpose of this study is to describe the uniqueness of the home yard in ecological tourism area of Puspa Jagad. This research was conducted in ecological tourism area of Puspa Jagad Semen Village, Gandusari District, Blitar Regency. Data collection was done by observation to the types of plants composing home yard. Interview was conducted to obtain data about the management of home yard and cultural aspects in it. Based on the benefits of these crops, the cultural value (ICS) and the value of UVS plant crops each. Based on observations, it is known that the diversity of plants in the home yard contained 151 species of 132 genus and 61 plant families. These plants are grown in general to beautify the atmosphere of the house. The stratified plant canopy vertebration in home garden in Ecology Puspa Jagad is dominated by strata III, II, and I. Based on the results of the calculation of ICS or Cultural Interest Index shows that the needs of the community depends largely on the local natural resources around. Based on the value of ICS and UVS, coconut and banana plant have the highest value.Keywords: ICS, identity, plant, UVS.